Admissible perturbations of α‐ψ‐pseudocontractive operators: convergence theorems. (1st July 2016) - Toscano, Elena; Vetro, Calogero
Abstract : We prove some convergence theorems for α ‐ ψ ‐pseudocontractive operators in real Hilbert spaces, by using the concept of admissible perturbation. Our results extend and complement some theorems in the existing literature. Copyright © 2016 John Wiley & Sons, Ltd.